The silent world of assisted reproduction: A qualitative account of communication between doctors and patients undergoing in vitro fertilisation in Australia - Louis Taffs; Ian Kerridge; Wendy Lipworth (Wiley, 2023)
Abstract Context In vitro fertilisation (IVF) is now a common assisted reproductive technology (ART) procedure globally, with 8 million children alive today having been conceived utilising IVF. For many patients, IVF is a difficult experience with many discontinuing treatment because of emotional, relationship and financial stress, or intolerable physical side effects of hormone treatments. Design and Participants A qualitative study, in which 31 professionals and 25 patients from the ART sector in Australia were interviewed. The interviews were analysed using codebook thematic analysis. Results Our data indicates there are 'silences' within the therapeutic relationship of IVF, which may limit the capacity for patients to prepare emotionally, financially, or medically for the procedure, and may contribute to psychological distress and dissatisfaction with care. These 'silences' include what the patient 'is not told' by their clinician or 'does not hear' and what the patient feels they 'cannot say'. Discussion Drawing upon the work of Jay Katz, Charis Thompson, and Miles Little on 'silences' and performance in clinical practice, we argue that although IVF is a complex and multifaceted procedure that is often conducted in a commercial setting, the clinical and therapeutic relationship between doctor and patient remains pivotal to the experiences of patients. The 'silences' within this relationship may impact negatively on decision‐making, and on the delivery and experience of care. Conclusions Careful attention to the realities of IVF treatment in the clinic room (and awareness of the performances that hide them) should allow for more present and compassionate care. Such care may leave patients more satisfied with their experience and their choices, regardless of treatment outcomes. Patient or Public Contribution This article draws on interviews with patients who had undergone or were currently undergoing IVF, as well as a range of representatives from the ART community (including reproductive medicine specialists, general practitioners, fertility nurses, counsellors, administrators in ART businesses and embryologists).